Math Graduate Students’ Information Behavior and Their Need for Information Literacy Instruction - Li, Ping (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This longitudinal study aims at finding out the information behavior of math graduate students at different stages of their programs. Data will be collected via semi-structured interviews, diaries and direct observations. Findings are expected to throw light on the designing of an effective instructional program for this group of users. Cette étude longitudinale a pour objectif de déterminer le comportement informationnel des étudiants en mathématiques de cycles supérieurs à différentes étapes de leur programme. Les données seront recueillies au moyen d’entrevues semi structurées, de journaux et d’observation directe. Les résultats devraient éclaircir la conception d’un programme d’enseignement efficace pour ce groupe d’utilisateurs.